Kan djævle klassificeres? - Vad, Annedorte (Hikuin, 2007)
Can the Devil be Classified? By Annedorte Vad The medieval wall paintings are a vast source of information on the ideas and thinking of the medieval man. To use the images as a source to the past it is necessary to view the images as a whole. That can be done using image databases where the images are classified according to their content. The Internet and image databases give the viewer of today the possibility to see millions of images with hundreds of years apart and from a vast geographical area at the same time on a computer. That opens op for comparing and analysing the content. Classification of images traditionally has its roots in written material and several aspects of the image content is never recorded or classified. The devil is one of those. This article shows how it is possible to find the devil in the wall paintings and subsequently describing him and saying some things about the mentality behind the representation.